Educational Transformation: Optimization in the Teaching of Logistics in International Business through the Application of Artificial Intelligence in Higher Education Institutions - Albarracín Vanoy, Ricardo Javier (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This study focuses on "Educational Transformation: Optimization in the Teaching of Logistics in International Business through the Application of Artificial Intelligence in Higher Education Institutions". The research addresses the need to adapt academic training to the changing demands of the global business environment, especially in the field of logistics in international business. It is proposed to explore the integration of artificial intelligence (AI) as a catalyst to optimize teaching in higher education institutions. The methodology used includes the review and analysis of academic research, case studies and practical experiences related to the application of AI in logistics teaching. It focuses on the population of higher educational institutions offering programs in logistics and international business, and the sample is selected in a stratified manner to address the diversity of pedagogical approaches and educational levels. Preliminary results suggest that the implementation of AI-based tools, such as simulations and predictive analytics, has significantly improved students’ acquisition of practical skills. Interactivity and participation have also seen a notable increase. Despite the challenges associated with teacher training and ethical educational data management, research suggests that the integration of artificial intelligence in logistics teaching represents a positive evolution in academic training, effectively preparing students for the Logistical challenges of the global business landscape.